Analisis Sistem Pentanahan Transformator Distribusi Di Fakultas Teknik Universitas Riau - Fitriyanto, Aidil; Firdaus, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Today the need for electrical energy increases in term of supporting people’s lives, the needs for electrical of household, colleges, and industries. To distribution the electricity from producers to consumers there is often blackout due to grounding is not achieved the standard, so when a fault occurs fault current cannot be through to ground well. This research proposes to analyze the Distribution Transformer Grounding System at Engineering Faculty of Riau University. To find out whether resistance grounding of the transformer achieved the standard, to protect people who where passing or touching equipment around the transformer from the danger of shock electricity when a fault occurs. Method of this research is collecting parameter ρ, ρs, RN by measurement, calculating using the formula of grounding resistance, touch voltage, step voltage, and power losses. Then, the analysis was carried out and compared IEEE Std 80 : 2000. The results of measurement, got the highest resistance is 5 Ω did not achieved the standar and got the lowest resistance is 1 Ω this achieved the standard of ≤ 1 Ω. The touch voltage with the highest resistance 5 Ω in fault current 10,311 A is 51,555 V, this value did not achieved the standard touch voltage ± 70 Kg is 998.29 V and touch voltage ± 50 Kg is 737.59 V. The step voltage with the highest resistance 5 Ω in fault current 10,311 A is 51,555 V, this value did not achieved the standard step voltage ± 70 Kg is 3,327.05 V and step voltage ± 50 Kg is 2,458.2 V. Power losses in the neutral conductor of Transformer I is 42.8 watt and Transformer II is 32 watt, the standard of below 500 watt. The data obtained, grounding resistance of the distribution transformer at Engineering Faculty of Riau University not according to IEEE Std 80 : 2000.Keywords : Grounding, touch voltage, step voltage, power losses.